Dewatered Sludge Decorated with Nanoparticles for Alum Sludge Conditioning towards the Concept of “End-of-Waste” - Hossam A. Nabwey; Maha A. Tony (Nanomaterials, 2023)
The circular economy concept is leading environmental engineering in the search for “End-of-Waste” criteria. Untreated waste residue results from drinking water treatment plants, causing severe environmental issues, and its reuse is essential. In this regard, this investigation introduces the beneficial reuses of alum sludge cake to close the loop between sludge waste generation and reuse. Considering alum sludge as a resource for dewatering instead of its categorization as a waste reflects an “End-of-Waste” approach. Alum sludge cake was thermally calcined at 400 °C and named thermally treated alum sludge cake (TAS-cake). In this study, TAS-cake decorated with magnetite with a percent weight of 5 to 1%, respectively, was labeled as TAS-cake@Fe-(5-1). X-ray diffraction (XRD) and morphologies were applied to characterize the hybrid composite. A Fenton-based hybrid composite was applied to extrude water from alum sludge for 7 min of conditioning time. Furthermore, the factorial design based on response surface methodology (RSM) was applied to optimize the operational variables. TAS-cake@Fe-(5-1) and hydrogen peroxide revealed 1.2 g/L and 740 mg/L doses at pH 3.0, showing pronounced performance and revealing the highest capillary suction time (CST) reduction, which reached 53%. A temperature increase also showed a pronounced enhancement effect on the sludge dewaterability that reached 72% when 55 °C was applied. Thus, such a novel conditioner is a promising candidate for alum sludge conditioning.